Solusi Financial Technology Syariah Terhadap Persoalan Keuangan Anggota Koperasi Karyawan - Nuruddin Muhammad Ali; Euis Amalia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study is to seek Islamic financial solution for members of employee cooperative in a particular firm by using Financial Technology platform which meet sharia terms and conditions. Methodology is Using the existing literature on FinTech and incorporating these contributions into a traditional Islamic financial structure, characteristics are outlined and placed into a framework that describes the industry. The findings that Islamic P2P Financing could propose a solution for financial problem faced by employee who need with limited amount for short period of time which Islamic banks could not provide. The findings of the study serve as a reference to industry players and regulators in formulating peer to peer financing for employee cooperative members and other similar cooperatives. This paper contributes by defining FinTech in Islamic finance and proposes term peer to peer financing instead of peer to peer lending which is not suitable with the nature of Islamic finance.